2015
DOI: 10.1039/c5dt03575a
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical characterization of a series of N5-based aromatic hyperhalogen anions

Abstract: Hyperhalogens are a class of highly electronegative molecules whose electron affinities even exceed those of their superhalogen ligands. Such species can serve as new oxidizing agents, biocatalysts, and building blocks of unusual salts, and hence are important to the chemical industry. Utilizing stable N5(-) as the ligand, a series of aromatic hyperhalogen anions, namely mononuclear M(N5)(k+1)(-) (M = Li, Be, B) and dinuclear M2(N5)(2k+1)(-) (M = Li, Be), have been reported here for the first time. Calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…39 Recently, two series of hyperhalogen anions involving planar and cage-like superhalogen ligands were reported, respectively, and the concept of aromatic hyperhalogen was brought forward as well. 40,41 In this work, theoretical investigation of borates of the rst three subgroup elements, namely scandium, titanium, and vanadium, was presented. On the one hand, these transition metal (TM) elements have unlled d orbitals, which may render the resulting compounds magnetism.…”
Section: Introductionmentioning
confidence: 99%
“…39 Recently, two series of hyperhalogen anions involving planar and cage-like superhalogen ligands were reported, respectively, and the concept of aromatic hyperhalogen was brought forward as well. 40,41 In this work, theoretical investigation of borates of the rst three subgroup elements, namely scandium, titanium, and vanadium, was presented. On the one hand, these transition metal (TM) elements have unlled d orbitals, which may render the resulting compounds magnetism.…”
Section: Introductionmentioning
confidence: 99%
“…Li and coworkers demonstrated that the molecules with loosely bound excess electrons (such as electride and alkalide molecules) exhibited large NLO response. In 2004, two theoretical papers have been reported, indicating that the hydrogen fluoride trimer anion ((FH) 2 {e} (HF)) and the water trimer anion ((H 2 O) 3 {e}) with excess electron exhibited significantly large static first hyperpolarizabilities ( β 0 ) . For instance, the β 0 value was found to be 1.72 × 10 7 au for (H 2 O) 3 {e} anion, which was dramatically larger than that of (H 2 O) 3 (only 35 au) and (H 2 O) 3 F – (only 46 au) .…”
Section: Introductionmentioning
confidence: 99%
“…gens" M(N 5 ) k + 1 (M = Li, Be, B). [48] It is expected that these species could lead to the synthesis of new superoxidizing agents. Up to now,t he ligands of superhalogens/hyperhalogens have evolved from conventional halogen atoms [24][25][26][27][28][29][30][31][32][33][34] into linear groups (such as CN, SCN, and BO 2 ) [35][36][37][40][41][42][43][44][45] and then into planar groups (such as NO 3 ,V O 3 ,a nd N 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Up to now,t he ligands of superhalogens/hyperhalogens have evolved from conventional halogen atoms [24][25][26][27][28][29][30][31][32][33][34] into linear groups (such as CN, SCN, and BO 2 ) [35][36][37][40][41][42][43][44][45] and then into planar groups (such as NO 3 ,V O 3 ,a nd N 5 ). [39,42,48] Therefore, an interesting question emerges:c an such speciesb ec onstructed by using molecular cages as ligands?T oa nswer this question, the polyhedral fluorocarbon cages became the focus of our attention.A st hese molecularc ages have as ufficient interiora ttractive potential, they can serve as the electron hole. Recently, it was reported that an excesse lectron can be trapped inside fluorinated fullerenes, such as C 60 F 60 and C 20 F 20 , [49] to form the molecular-solvated electrons e@C 20 F 20 and e@C 60 F 60 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation